2015
DOI: 10.1007/s10995-015-1682-5
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in Inadequate Gestational Weight Gain Differ by Pre-pregnancy Weight

Abstract: Objectives Pre-pregnancy body mass index (BMI) varies by race/ethnicity and modifies the association between gestational weight gain (GWG) and adverse pregnancy outcomes, which disproportionately affect racial/ethnic minorities. Yet studies investigating whether racial/ethnic disparities in GWG vary by pre-pregnancy BMI are inconsistent, and none studied nationally representative populations. Methods Using categorical measures of GWG adequacy based on Institute of Medicine recommendations, we investigated wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 74 publications
2
28
0
Order By: Relevance
“…A global maternal anthropometry study that considered births found that weight gain was significantly associated with birth weight and intrauterine growth 11. Moreover, mothers with pre-gestational weights of <40 kg were 3 times as likely to have SGA babies than those with pre-gestational weights of ≥40 kg 18. Another study in rural India showed that pregnant women with weights of <45 kg were at higher risk of giving birth to low-weight newborns, compared to women with weights of >45 kg 19.…”
Section: Discussionmentioning
confidence: 99%
“…A global maternal anthropometry study that considered births found that weight gain was significantly associated with birth weight and intrauterine growth 11. Moreover, mothers with pre-gestational weights of <40 kg were 3 times as likely to have SGA babies than those with pre-gestational weights of ≥40 kg 18. Another study in rural India showed that pregnant women with weights of <45 kg were at higher risk of giving birth to low-weight newborns, compared to women with weights of >45 kg 19.…”
Section: Discussionmentioning
confidence: 99%
“…610 Additionally, a higher proportion of women who identify as NH black or African American begin pregnancy obese and, if underweight or normal weight, gain below the Institute of Medicine (IOM) gestational weight gain recommendations, compared with NH white women. 11,12 Previous studies of weight gain and preterm birth have been limited by the methods available to account for the fact that women who deliver preterm have less time to gain weight during pregnancy, and these studies have not focused on racial/ethnic differences except in very limited study samples. 1315 …”
Section: Introductionmentioning
confidence: 99%
“…In general, nulliparous women are more likely to have higher gestational weight gain, and this demographic difference may have influenced our findings . The influence of ethnicity on gestational weight gain is complex and likely mediated by prepregnancy BMI . Our sample size was not large enough to evaluate the potential interactive effects of race and ethnicity and type of prenatal care on breastfeeding outcomes.…”
Section: Discussionmentioning
confidence: 95%